Canine bruellosis (Veterinary Science, 2017)
Canine brucellosis caused by Brucella canis is a contageous and infectious disease that affects dogs. It has been diagnosed in EEUU and several other coutries, including Russia, Japan, Nigeria, India, China and Argentina. Natural infection can occurs by vertical or horizontal route, by means of seminal or vaginal secretions and by oronasal and conjunctival mucous. The most significating sign of the disease is abortion and reproductive failure in females and orchitis and epididimitis followed by infertility in males. The diagnosis is based on isolation of the bacteria from hemoculture and serologic tests with specific antigens of Brucella canis. The treatment is expensive, extended and not 100% effective, and the infection often reccurs after it. The transmission of Brucella canis to man commonly occurs through contact with infected dogs or their secretions or through direct laboratory exposure, but is not frequent and is easily treated.
Keywords: Canine bruellosis